2016
DOI: 10.1080/14719037.2016.1200665
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of informal governance on political innovation

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 Assessing the impact of informal governance on political innovation ABSTRACTThe aim of this article is to examine the role played by 'informal governance' in shaping political innovation. Informal governance can be defined as a means of decision-making that is un-codified, non-insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…Communications and engagement staff, trained in marketing, demonstrated little awareness of user-survivor movements (Barnes and Cotterell, 2010) or empowerment, as the contentious encounter with wider voluntary sector groups showed. The disparate views of members who may have either supported or campaigned against the imposition of new models of healthcare went unrecognised as consensus became a form of governmentality, reinforced through the ritual of tea, biscuits, humour and non-decision making practices (Ayres, 2017). Thus, as Alderwick et al found, "difficult decisions [were] easy to avoid" (Alderwick et al, 2016: 25).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Communications and engagement staff, trained in marketing, demonstrated little awareness of user-survivor movements (Barnes and Cotterell, 2010) or empowerment, as the contentious encounter with wider voluntary sector groups showed. The disparate views of members who may have either supported or campaigned against the imposition of new models of healthcare went unrecognised as consensus became a form of governmentality, reinforced through the ritual of tea, biscuits, humour and non-decision making practices (Ayres, 2017). Thus, as Alderwick et al found, "difficult decisions [were] easy to avoid" (Alderwick et al, 2016: 25).…”
Section: )mentioning
confidence: 99%
“…These bureaucratic artefacts (minutes, agendas, action log) presented a business-like image but the more casual meeting culture constituted a practice of 'informal governance' (Ayres, 2017 This acknowledgement of possible contention was, however, usually glossed over as meetings operated with an informal culture of apparent consensus, described by the Programme Director as 'a group of friends' (fieldnotes). Internal processual issues dominated many meetings and the Group reviewed its terms of reference three times within two years.…”
Section: I Was Part Of the Planning Of This … It Has Got A Seven-ymentioning
confidence: 99%
See 1 more Smart Citation
“…The first relates to Bulpitt's focus on 'Court politics' and the small number of key individuals that form the decision-making political elite. In relation to post-2015 English devolution, the 'Court' was very small with the policy being personally associated with and driven by one person: George Osborne (Ayres, 2017). This might explain the manner in which several Whitehall departmentse.g., the departments for Education and Skills and Work and Pensions -seemed reluctant to engage in devolutionary discussions and why negotiations over specific policy areas (e.g., housing, pre-16 education etc.)…”
Section: Rq1 What Territorial Management Code Has Shaped English Devmentioning
confidence: 99%
“…Devolution of power features potential conflict amongst those negotiating, an uncertain context, and a 'large numbers' problem (Ayres, 2017), all incentivising a back stage approach. This appears to have been the rationale adopted during George Osborne's term as Chancellor of the Exchequer (May 2010-July 2016).…”
Section: Part I Policy Contextmentioning
confidence: 99%